2021
DOI: 10.31234/osf.io/auy69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the automaticity of syntax using masked visual priming

Abstract: Language comprehension proceeds at a very fast pace. It is argued that context influences the speed of language comprehension by providing informative cues for the correct processing of the incoming linguistic input. Priming studies investigating the role of context in language processing have shown that humans quickly recognise target words that share orthographic, morphological, or semantic information with their preceding primes. How syntactic information influences the processing of incoming words is howe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Conversely, a determiner in the nominative case would suggest the analysis of the upcoming word via a lemma search, which takes equal time for nouns and verbs. Indeed, in Experiment 3 Pyatigorskaya et al (2021) showed no automatic syntactic priming when the target verbs were irregular forms, which are not morphologically decomposed. Overall, this study supports the notion that syntactic context can automatically influence how categories are accessed (Experiment 2) and that grammaticality effects rely, for some type of constituents, on morphological marking.…”
Section: Pre-lexical Versus Post-lexical Processingmentioning
confidence: 85%
See 4 more Smart Citations
“…Conversely, a determiner in the nominative case would suggest the analysis of the upcoming word via a lemma search, which takes equal time for nouns and verbs. Indeed, in Experiment 3 Pyatigorskaya et al (2021) showed no automatic syntactic priming when the target verbs were irregular forms, which are not morphologically decomposed. Overall, this study supports the notion that syntactic context can automatically influence how categories are accessed (Experiment 2) and that grammaticality effects rely, for some type of constituents, on morphological marking.…”
Section: Pre-lexical Versus Post-lexical Processingmentioning
confidence: 85%
“…2 We here use the general term "syntactic priming", as in the first (Goodman et al, 1981) and most recent (Berkovitch & Dehaene, 2019;Pyatigorskaya et al, 2021) applications of the paradigm. To avoid confusion, we make it explicit here that the effect we describe is different from the structural priming effect (Bock, 1986), sometimes also called "syntactic priming", which refers to the facilitation observed in processing or producing two sentences with the same grammatical structure.…”
Section: Syntactic Violationsmentioning
confidence: 99%
See 3 more Smart Citations